Analisis Dampak Pendampingan Spiritual Terhadap Kesehatan Mental Pasien Kronis Pada RSUD Meuraxa - Fitri Ramadayanti; Ismiati; Zamratul Aini (Ameena Journal, 2026)
Patients with chronic illnesses are affected not only physically but are also vulnerable to mental health problems such as anxiety, stress, fear, and difficulty accepting their medical condition. The prolonged treatment process often causes psychological distress that affects patients' emotional and social well-being. One effort to address these problems is through spiritual care. This study aimed to examine the process of spiritual care and analyze its impact on the mental health of chronic patients before and after receiving spiritual care at Meuraxa Regional General Hospital. This study employed a qualitative method with a descriptive research design. The research participants consisted of two spiritual counselors and seven chronic patients who had received spiritual care. The findings revealed that the spiritual care process was carried out through personal and intrapersonal approaches integrated with religious values, including dhikr (remembrance of Allah) and prayer. Spiritual care was provided regularly through visits to inpatient wards by assigned spiritual care teams. Before receiving spiritual care, most patients experienced anxiety, stress, fear, difficulty accepting their illness, and a loss of motivation to undergo treatment. After receiving spiritual care through prayer, dhikr, salawat (blessings upon the Prophet Muhammad), spiritual motivation, religious counseling, and worship guidance, patients demonstrated improvements in their mental health, including reduced levels of anxiety and stress, increased self-acceptance, greater inner peace, and enhanced motivation and hope to continue their treatment. The study concludes that spiritual care has a positive impact on the mental health of patients with chronic illnesses and serves as an important component of holistic healthcare that supports the patient recovery process at Meuraxa Regional General Hospital.